2015
DOI: 10.3136/fstr.21.685
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Degradation by Some Bacteria Isolated from Food

Abstract: The study aimed to isolate and characterize probiotic strains with potential cholesterol degrading activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
0
0
2
Order By: Relevance
“…Therefore, the current study results are compatible with many studies that proved the ability of different bacteria to reduce cholesterol in a liquid media, such as [8], who reported that bacterial isolated from raw cow milk demonstrated cholesterol degradation activity. In addition, it is consistent with a previous study that indicated theLactobacillius isolates have the potential to diminish cholesterol [15] . Isolate No8 was characterized according to Bergey's Manual of Systematic Bacteriology [9] as the genus lactobacillus .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the current study results are compatible with many studies that proved the ability of different bacteria to reduce cholesterol in a liquid media, such as [8], who reported that bacterial isolated from raw cow milk demonstrated cholesterol degradation activity. In addition, it is consistent with a previous study that indicated theLactobacillius isolates have the potential to diminish cholesterol [15] . Isolate No8 was characterized according to Bergey's Manual of Systematic Bacteriology [9] as the genus lactobacillus .…”
Section: Discussionsupporting
confidence: 92%
“…배양액(1 mL)에 BA 혼합 표준용 액(500 mg/L) 및 0.4 M perchloric acid(9 mL)를 첨가하여 진탕 혼합한 다음 원심분리(3,000 ×g, 10분)하였다. 상등액을 여과 (Whatman paper No (Khiralla, 2015 (Cousin 등, 2011;Li와 Cao, 2010). 하지만 인공 소화액에 대한 저항 성, 상피세포에 대한 부착능 및 항균물질 생산능 등 프로바이 오틱 균주로서 기본적인 조건을 갖추었다고 할지라도 BA와 같은 독성 물질을 생성하지 않아야만 안전하게 이용할 수 있 으므로 발효 식품 제조에 이용하기 전에 아미노산 탈탄산 효…”
Section: Ba 분해능 측정unclassified
“…2013, Pattani και συν. 2013, Skokovic-Sunjic 2014, Reid 2015 και η μείωση των επιπέδων χοληστερόλης στο αίμα (Mahrous 2011, Khiralla 2015, Guan και συν. 2017.…”
Section: εισαγωγηunclassified